The aeropalynology of Es-Sénia airport, Oran, northwest Algeria. (2nd January 2017) - Kiared (Ould-Amara), Ghania; Bessedik, Mostefa; Riding, James B.
Abstract : A continuous study of atmospheric pollen in Oran Province, northwest Algeria, using the Cour method was undertaken between April 2004 and April 2006. A pollen-collecting device was placed in the meteorological station at Es-Sénia airport, near Oran city. It was found that the pollen harvest during the first year was 4230 grains, which is significantly higher than that in the second year which produced 2258 grains. These data gave a mean annual index of 3246 pollen grains, 99.7% of which were positively identified. Pollen from herbaceous plants (69.5%) proved significantly more abundant than arboreal and shrub pollen (27.9 and 2.3% respectively). The pollen types identified, in decreasing order of abundance, were Chenopodiaceae/Amaranthaceae, Plantago, Olea, wild Poaceae, Lygeum, Cupressaceae, Urticaceae, Quercus, Pinus, total Asteraceae, Eucalyptus, Brassicaceae, Casuarina, Pistacia, Arecaceae, Apiaceae, Thymeleaceae and Rumex . The abundance range was Chenopodiaceae/Amaranthaceae (41.4%) to Rumex (0.6%). The winter pollen spectrum largely comprised Arecaceae and Cupressaceae. Pollination during spring included most taxa, i.e. total Asteraceae, Brassicaceae, Chenopodiaceae/Amaranthaceae, Lygeum, Olea, Pinus, Pistacia, Plantago, wild Poaceae, Quercus, Rumex and Urticaceae. During the summer Apiaceae and Eucalyptus both pollinated, and Casuarina pollen was largely produced in autumn. A significant correspondence between the airborne pollen spectrum and the vegetation of the region was established.